Grain price stabilization experiences in Asia: what have we learned?” - Cummings, Jr. , Ralph; Rashid, Shahidur; Gulati, Ashok (Elsevier, 2006)
Governments in most Asian countries used grain price stabilization as a major policy instrument when they embarked on promoting the Green Revolution. The art of public policy-making is to know when to introduce government interventions and when to withdraw. The common mistake is to forget the withdrawal part, leading to unsustainably high costs – a dilemma that most Asian countries are confronted with today. Analyzing case studies of six Asian countries, which have tried to tackle the task in different ways with varying degrees of success, eight key lessons can be learned from the more than three decades of food price stabilization in Asia. Times have changed: policies and public agencies that may have been appropriate 30 years ago are not optimal today. Private institutions have strengthened significantly – or could be strengthened significantly – and should be entrusted for many of the functions that parastatals, or other government agencies, have traditionally performed. Holding on to old practices delays reaping the benefits that changing current policies have to offer.